Assessment of School health programs using oral health integrated health promoting school framework in Bengaluru (Southern India) - a cross-sectional compliance study - Sagarkar, Dr. Anitha R.; K, Dr. Pushpanjali; Gadicherla, Dr. Suman; Krishnappa, Dr. Lalitha (South Eastern European Journal of Public Health, 2024)
Schools play a crucial role in promoting health, reaching more than one billion children worldwide and providing an ideal setting for establishing lasting health habits (1). School-age is fundamental for developing knowledge, attitudes, and behaviors related to general and oral health, making schools vital for targeted health initiatives (2,3). Given that children typically spend 6–7 hours daily in school, health interventions aimed at this demographic have the potential to substantially enhance not only their own well-being but also that of their families and the wider community (4, 5).